Entre trincheiras narrativas: as encruzilhadas de Pepetela - Santos, Jeferson Rodrigues dos (2025)
This thesis articulates the concept of the “crossroads” as a counter-narrative strategy in Pepetela's novels, fundamentally establishing it as the central critical-analytical method of this study. By tracing political and aesthetic aspects in the author's works, this method reveals production tactics for a literature of resistance that simultaneously revises and questions the colonizing gaze. With this, it constitutes an Afro-literary approach that operates as an aesthetics of reconstruction, in which voices and knowledges meet, create tension, and project ways out of the social and political chaos inherited from colonialism (Martins, 2021; Rufino, 2019; Mbembe, 2011, 2016; Sodré, 2017; Padilha, 2002; Nkosi, 1981; Thiong'o, 1997; Gilroy, 2001; Glissant, 2021). The analysis is informed by post-colonial studies (Prince, 2005; Said, 2005, 2011; Bhabha, 2013; Spivak, 2010), decolonial approaches, and counter-colonial theories (Piglia, 1990; Mignolo, 2003; Quijano, 2009; Grosfoguel, 2007; Sousa Santos, 2002), as well as by the critical reception of literatures in the Portuguese language (Chaves, 1999, 2005; Laranjeira, 1995, 2023; Trigo, 1981; Mata, 1993, 2001, 2007; Leite, 2003, 2012; Lanzieiro, 2020). Based on this framework, the present study applies the methodological prism of the crossroads to the novels Muana Puó (1978), Mayombe (1980), Yaka (1984), Se o Passado Não Tivesse Asas (2016), and Sua Excelência, de Corpo Presente (2018). Structured in three parts, the thesis first establishes the theoretical-contextual foundations and maps the tradition of Angolan counter-narrative ; it then situates the narrators' trenches within the post-colonial context, highlighting their positions in Mayombe and the post-colonial-colonial enunciating subject in Sua Excelência, de Corpo Presente ; finally, it explores the crossroads as a narrative and structural device, analyzing it through three relational dynamics: the “encounters” in Muana Puó (voices, cultures, perspectives), the “circularities” in Yaka (memory, history, identities), and the “spiralities” in Se o Passado Não Tivesse Asas (memory, identity, updating of futures). As a result, it is demonstrated that Pepetela's narrative crossroads, read through this method, weave a space of resistance and renewal of the novelistic form itself, also contributing to the Africanization of the literary field.